Risk Factors of Growth Faltering on Infants Aged 6-12 Months in Tongkuno, Southeast Sulawesi - Thamrin, Jumianti Lestari; Kartasurya, Martha Irene; Sakundarno, Mateus; Mexitalia, Maria; Suhartono, Suhartono (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Background: The prevalence of underweight and severe malnutrition on under-five children in Southeast Sulawesi based on the latest Riskesdas was 23.9%, which higher than the national prevalence (19.6%). This study aimed to analyze risk factors of growth faltering on infants aged 6-12 months in Tongkuno. Methods: This was a cohort prospective study. The numbers of subjects were 79 infants: 32 infants who were given early complementary feeding and 47 infants who were not. Consecutive sampling technique was used in this study. The adequacy levels of energy and protein intake were collected using 2x24 hours food recall. The incidence of upper respiratory tract infection was recorded through interviews using structured questionnaires. Data were analyzed by logistic regression method. Results: There were 46.9% of the infants who had growth faltering among the early complementary feeding group. Multivariate analysis showed that the early complementary feeding, low levels of energy adequacy, and frequent URTI were the risk factors for growth faltering. The frequent URTI was the most influential factor for growth faltering (OR= 5.52; 95%CI: 1.63-18.72). Conclusion: The frequent URTI was the most important factor for growth faltering on infants aged 6-12 months in Tongkuno. Increased exclusive breastfeeding promotion and URTI prevention are recommended. Keywords: Risk factors, Growth faltering, Infants